HUBUNGAN TEKNIK MENYUSUI, SENDAWA BAYI, DAN PEMBERIAN SUSU FORMULA DENGAN FREKUENSI REGURGITASI PADA BAYI USIA 0-6 BULAN - Ulva Noviana (Jurnal Kesehatan dr. Soebandi, 2017)
Regurgitation is a clinical symptom often found in babies suffering from reflex gestroesofagus (RGE). At Polindes Gingging Bluto Sumenep on 10 Desember, of 10 mothers of 0-6 month-old babies, through interview, said that their babies experienced regurgation more than three times a day. The objective of research was to analyze the relationship of breastfeeding technique, belching technique, and bottle feeding with frequency of regurgitation for 0-6 month old babies. This research employed a cross sectional design. Independent variable was breastfeeding technique, belching technique, and bottle feeding and dependent variable was frequency of regurgitation for 0-6 month old babies. Population consisted of 43 respondents. Sampel which used simple random sampling technique consisted of 39 respondents. Data collection technique used observation sheets and questionnaires. Data analysis technique used statistic test of spearman rank and lamba. Spearman rank test showed that between breastfeeding technique and frequency of regurgitation was relationship was ρ value = 0,001 (sig< α = 0,05). It meant that there was relationship between breastfeeding technique and frequency of regurgitation. In belching technique was ρ value = 0,00 (sig < α = 0,05). It meant there was relationship between belching technique and frequency of regurgitation. Spearman rank test showed that between bottle feeding and frequency of regurgitation was ρ value = 0,00 (sig < α = 0,05). It meant that there was relationship between bottle feeding and frequency of regurgitation. Midwives, as motivators in midwifery care, have to improve their roles in giving guidance of regurgitation and way of treatment such correct breastfeeding technique, correct belching technique and ASI exclusive breastfeeding very useful for baby growth and development.